SPECTRUM OF HEMATOLOGICAL DISORDERS IN BONE MARROW EXAMINATION - SANJANA, NUTAKKI; CHERUKURI, PRASANTHI; GARDAS, VASUNDARA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To study the bone marrow aspiration (BMA) trends and to observe and analyze the various patterns of hematological disorders in bone marrow examinations of patients attending a tertiary care teaching hospital. Methods: A 2-year study was done retrospectively in the department of pathology at the tertiary care teaching hospital. Relevant demographics, clinical details, intraprocedural details, and results were obtained through records and case files. Results: A total of 48 cases were studied. The most common diagnoses recorded were erythroid hyperplasia, nutritional anemia, megaloblastic anemia, acute leukemias, etc. Conclusion: Bone marrow cytology is a highly informative and diagnostic test procedure performed in evaluating blood and blood-related diseases. Some hematological conditions can be diagnosed with serological studies, and the need for an invasive test like BMA can be avoided.